Temporal comparison of ocular blood flow in quadrant divisions of optic nerve head before and after water drinking test - Bhatti, M.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Water drinking test is used as stress test for glaucoma, as it produces changes in intra-ocular pressure. Laser speckle flowgraphy (LSFG) system is used to assess blood flow changes in four regions of the optic nerve head in this study. The LSFG system is a relatively new and simple blood flow measuring technique that displays optic nerve head vascular maps providing relative blood flow readings. The results show significant changes in blood flow of the four regions of the optic nerve head namely, superior, inferior, temporal and nasal after drinking water. These changes are important to further the current understanding of auto-regulation phenomenon after water drinking test in healthy subjects. This data can serve as an important baseline data for comparison with patients displaying glaucoma onset and progression. © 2016 IEEE.